Serviços multimídia em redes de 3ª geração e aspectos que influenciam a utilização da vídeo-telefonia móvel - Fernandes, Jeferson Lisboa (2008)
Since the first 3G mobile network based on UMTS standard on November of 2007, most of the Brazilian mobile operators is deploying nationwide 3G networks. This moment implies huge changes in local market, once mobile broadband services provided by 3G are fulfilling the gap of a low penetration service in the country. Besides, the 3rd generation is responsible for providing new multimedia experiences to the mobile users due to the increasing of capacity of its packet network. This study is specially focused on two multimedia services: Mobile TV and Mobile Video-Telephony. For these services, the study discusses technological and market aspects. The other and main objective of the study is related to the mobile video-telephony. The ability of communicating with audio and video at the same time takes the personal communication to a totally different level of end-user experience. Associated to this experience, the study identifies aspects, related to the human behavior and practical issues, which imply positive or negative influences on the use of the service. In order to identify the aspects, the study proposes a field questionnaire to be responded by Brazilian users with mobile video-telephony experience.